Growth and spatial patterns of natural regeneration in Sierra Nevada mixed-conifer forests with a restored fire regime - Fertel, Hannah M.; North, Malcolm P.; Latimer, Andrew M.; Ng, Jan (Forest ecology and management, 2022)
•Forests with a restored fire regime had high natural regeneration rates.•Regardless of species, the majority of sampled stems, were found in clumps.•Young trees in clumps had higher diameter and height growth rates than individuals.•There was no significant difference in growth rates among clump sizes.•High shrub cover didn’t have a significant negative effect on seedling growth rates. Many dry conifer forests in the western United States were historically adapted to frequent low-to-moderate severity fires, but are increasingly susceptible to large, stand-replacing wildfires due to dramatically altered stand conditions and changing climate. The historic tree spatial patterns of mature stands in fire-adapted forests – individual trees, clumps of trees, and openings (ICO) – are associated with heightened resistance and resilience to fire. How this pattern develops over time, however, is not well understood and could help inform reforestation practices better designed to increase fire resistance in developing stands. We investigated growth rates and spatial patterns among regenerating trees in mixed-conifer forests with restored fire regimes in California’s Sierra Nevada. We compared average stocking densities across tree species, size classes, shrub cover, and fire histories. We also examined the effects of microsite topography on spatial patterning of these juvenile trees, and the effects of clump patterning, local stem density and adjacent shrubs on tree growth rates. We found that the majority (75%) of sampled stems were found in clumps. Our mixed-effect models indicated that for trees growing within clumps, increased crowding slowed tree growth, as expected. Surprisingly, however, compared with individual trees growing outside clumps, trees growing within clumps grew significantly faster. Shrub cover in proximity to juvenile trees did not have a consistent impact across our models, but was associated with increased annual height growth. Additionally, plots with high shrub cover had higher stocking rates among the tallest regenerating stems (height > 137 cm). Our findings indicate that clumped spatial patterns of natural tree recruitment may favor the establishment and early growth of regenerating conifers in active-fire forests. While our study focused only on the early stages (<30 years old) of regeneration, our results contrast with common reforestation strategies favoring regular, widely-spaced plantings and aggressive shrub reduction. Our research suggests we need a better understanding of how heterogeneity in the spatial patterns of juvenile trees and shrubs may enhance the resilience of regenerating stands as they mature.